ADAPTASI AKSESI KENTANG HITAM {Plectranthus rotundifolius (Poir.) Spreng} TERHADAP BERBAGAI INTENSITAS CAHAYA - Ning Wikan Utami; Albert Husein Wawo (BERITA BIOLOGI, 2012)
Light is one of limiting factors for plant growth, including black potatoes {Plectranthus rotundifolius (Poir.) Spreng}. This species is a potential carbohydrates source that has been utilized in some areas as an alternative food.Plant adaptation to light intensity is controlled by genetic potential and environment.The aim of this research is to obtain information about the light intensity that suitable for growing some black potato accessions and mutants. The study was compiled using Nested Randomized Complete Block Design.Five accessions (Solo, Sangian, Nganjuk, 6G and 25G) planted in 3 degrees of light intensity i.e. full light (N0), 70% (N1), 50% (N2) and 25% (N3).The results revealed that light greatly affect the growth and production of 5 accessions of black potatoes. Five accessions tend to tolerant for decreasing light intensity until 70%. Decreasing in growth and yield characters significantly occurred in 25% of light intensity than control. Solo and Sangian stable to 4 light intensity treatments.